2017
DOI: 10.1111/ijcp.12996
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence with mirabegron vs antimuscarinics in overactive bladder: Retrospective analysis of a UK General Practice prescription database

Abstract: MIR was associated with a significantly longer time to discontinuation, greater persistence and better adherence than AMs. However, there was a steep decline in persistence with all drugs after 1 month. This is unlikely to be wholly explained by anticholinergic adverse events, as it was also seen with MIR. The lower proportion of MIR patients who were treatment-naive reflects current prescribing guidelines whereby MIR is prescribed after an initial generic AM trial. The study was limited by the small number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 24 publications
7
39
3
Order By: Relevance
“…In this situation, and/or if unacceptable adverse events occur, AUA guidelines recommend dose modification or a trial with another antimuscarinic, or a β3‐adrenoreceptor agonist such as mirabegron . Recent studies have shown increased persistence rates with mirabegron vs antimuscarinics in the UK, Canada, and Japan, suggesting an improved efficacy/tolerability balance for mirabegron vs antimuscarinics …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this situation, and/or if unacceptable adverse events occur, AUA guidelines recommend dose modification or a trial with another antimuscarinic, or a β3‐adrenoreceptor agonist such as mirabegron . Recent studies have shown increased persistence rates with mirabegron vs antimuscarinics in the UK, Canada, and Japan, suggesting an improved efficacy/tolerability balance for mirabegron vs antimuscarinics …”
Section: Discussionmentioning
confidence: 99%
“…19 Recent studies have shown increased persistence rates with mirabegron vs antimuscarinics in the UK, Canada, and Japan, suggesting an improved efficacy/ tolerability balance for mirabegron vs antimuscarinics. [22][23][24] It is recognized that treatment for LUTS has a high rate of discontinuation. 22,25,26 Among men, feeling of incomplete emptying (with or without bother) was associated with a higher chance of treatment discontinuation, while hesitancy and bother with post-micturition dribble were associated with a lower chance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that a greater persistence is obtained in those of retrospective design compared with the prospective ones (with patient follow-up), with the exception of a prospective case series of 354 patients, which showed a persistence of 25% at 12 months. 32 This current study's treatment review, based on safety and efficacy criteria, achieved a reduction in the IG leading to potential saving, as calculated from the official expenditure data provided by the public insurer (CatSalut). In the literature there are studies that evaluate the economic cost of OAB, although methodological differences do not allow comparisons, and the authors believe that caution should be employed in the generalisation of results.…”
Section: Intervention Groupmentioning
confidence: 96%
“…Conversely, mirabegron is a first-in-class selective oral β 3 -adrenoceptor agonist, and therefore does not contribute to ACB. Mirabegron has demonstrated similar efficacy as antimuscarinics but with improved tolerability in men and women ≥18 years of age with symptoms of OAB for ≥ 3 months [24][25][26] and, consequently, better persistence [27].…”
Section: Introductionmentioning
confidence: 99%